Penerapan Permainan Al-Asrar Al-Mutasalsilah Dalam Pembelajaran Maharah Istima’ di SMP Darussalam 2 Watukosek Gempol - Nasir Salasa; Hasan Syaiful Rizal (Universitas Yudharta Pasuruan, 2022)
This study aimed to determine the application of the whisper-chain game in learning Arabic listening skills, and the advantages and disadvantages of the whisper-chain game. This research uses a qualitative approach with the type of research using case studies. The data collection techniques used are observation, interviews, and documentation. Data analysis in this study uses data reduction, data display, and conclusion drawing or verification. The results of this study indicate that the application of the whisper-chain game conducted by the researchers at SMP Darussalam 2 Watukosek Gempol in Arabic listening skills was carried out well and succeeded in increasing the criteria for students' scores in Arabic listening skills. The strengths and weaknesses that exist are not so difficult for students and do not become an obstacle for teachers, so they can still be overcome with teacher performance skills. In each lesson, students were more focused on listening and listening to lessons other than Arabic subjects.